2014
DOI: 10.1161/circresaha.114.303784
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MicroRNA-155 Protects the Heart From Pathological Cardiac Hypertrophy

Abstract: Rationale In response to mechanical and/or pathological stress, adult mammalian hearts often undergo mal-remodeling, a process commonly characterized as pathological hypertrophy, which is associated with upregulation of fetal genes, increased fibrosis, and reduction of cardiac dysfunction. The molecular pathways that regulate this process are not fully understood. Objective To explore the function of microRNA-155 (miR-155) in cardiac hypertrophy and remodeling. Methods and Results Our previous work identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
108
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 33 publications
5
108
0
Order By: Relevance
“…[7][8][9] For instance, miR-155 may function as an inducer of pathological cardiac hypertrophy and its down-regulation might have potential therapeutic advantages. 10) miR-328 has been reported to promote cardiac hypertrophy and may serve as a promising therapeutic target for this disease. 11) Recently, the crucial roles of miR-10a in the pathological process of several diseases have been attracting increasing attention.…”
mentioning
confidence: 99%
“…[7][8][9] For instance, miR-155 may function as an inducer of pathological cardiac hypertrophy and its down-regulation might have potential therapeutic advantages. 10) miR-328 has been reported to promote cardiac hypertrophy and may serve as a promising therapeutic target for this disease. 11) Recently, the crucial roles of miR-10a in the pathological process of several diseases have been attracting increasing attention.…”
mentioning
confidence: 99%
“…In a previous study, we elucidated the feasibility of using our constructed miRNA reporter imaging system to monitor the location and magnitude of expression levels of miR‐22 in cardiac hypertrophy in vitro and in vivo 19. Most recently, miR‐155 was reported to be expressed in atherosclerotic plaques and proinflammatory macrophages and the in vivo function of miR‐155 in cardiomyocyte hypertrophy was also manifested 20, 21, 22. Another excellent study in this research area by Shyam's group demonstrated a previously unknown role for BRCA1 in epigenetic control of miR‐155 23…”
mentioning
confidence: 99%
“…In fact, coinheritance of the rs5068 and rs61764044 minor alleles in humans can be viewed as an experiment of nature that demonstrates the physiologic impact of these ANP-raising mechanisms on blood pressure and suggests therapeutic opportunities to increase ANP levels with potential benefits in hypertension or heart failure. Recent studies have implicated the therapeutic potential of miR-155 inhibition in suppressing cardiac hypertrophy and heart failure (28,29). Moreover, miR-155 levels were also reported to be increased in human hearts with hypertrophy compared to nonhypertrophic controls and increased miR-155 levels were correlated with depressed cardiac function and increased wall thickness (29).…”
Section: Discussionmentioning
confidence: 99%